Effects of Metoclopramide and Hyoscine-N-Butyl Bromide on Motility of Duodenum in Male Rats and Quantum Computational Analysis - Omar, Sleman Yousif; Kaçar, Emine; Mamand, Dyari Mustafa; Omer, Rebaz Anwar (TUBITAK, 2024)
Gastroenteritis accompanied by emesis commonly involves treatment with metoclopramide, a prokinetic agent. Conversely, hyoscine-N-butyl bromide (Buscopan), an anticholinergic compound, impedes acetylcholine’s interaction with muscarinic receptors. This study aimed to elucidate the effects of metoclopramide on duodenal motility induced by acetylcholine and to investigate the influence of metoclopramide alone and in combination with hyoscine-N-butyl bromide on duodenal contractility. Duodenal tissue segments, 1 cm apart, were prepared and secured with surgical silk at both ends within an isolated organ bath. Isometric contractions were recorded as the tissue was subjected to various treatments. Acetylcholine (10-4 M) was introduced initially, followed by the addition of metoclopramide (35 M), hyoscine-N-butyl bromide (15 M), and a combination of both (50 M) after a 10-minute incubation period. The responses of the duodenal tissue were characterized by changes in frequency, peak-to-peak amplitude, and amplitude. Additionally, quantum chemical calculations were performed to investigate several chemical properties, with a focus on determining the active center using the Fukui function. The study revealed that metoclopramide significantly enhanced duodenal motility induced by acetylcholine, as evidenced by a notable increase in frequency and amplitude of contractions compared to the control group (p < 0.05). Furthermore, the combination of metoclopramide and hyoscine-N-butyl bromide exhibited a synergistic effect, resulting in a more pronounced enhancement of duodenal contractility compared to either drug alone (p < 0.01). Quantum chemical calculations identified key chemical properties and elucidated the active center, providing insights into the molecular mechanisms underlying the observed physiological responses. © 2024, TUBITAK. All rights reserved.
Keywords: DFT; Duodenum; Hyoscine-N-Butylbromide; Metoclopramide